The Rate of Inflation: Implementation for Income of Household Business in Sampe Cita Village - Rangkuty, Dewi Mahrani; Sajar, Suryani; Yazid, Ahmad; Satria, Wisnu (The Eastasouth Journal of Social Science and Humanities, 2024)
The purpose of this study was to analyse access to capital and technology responsiveness at the inflation rate as a mediating variable on the income of household businesses in the Glugur Rimbun area (Case Study: Sampe Cita Village). The specific target of this study is to analyse the level of inflation rate as a mediating variable on the income of household businesses in the Glugur Rimbun area (Case Study: Sampe Cita Village). So that it can show the value of the influence of the inflation rate on the income of household businesses in the Glugur Rimbun area of Sampe Cita Village. The hypothesis in this study is the level of inflation rate as a mediating variable on the income of household businesses in the Glugur Rimbun area (Case Study: Sampe Cita Village). Access to capital and responsiveness to technology influence the income of household business owners in Sampe Cita Village, with the inflation rate serving as a mediating factor. This study will utilize quantitative data to assess how the inflation rate mediates the relationship between capital and technology access and the income of household entrepreneurs in the Glugur Rimbun area, specifically focusing on Sampe Cita Village. The data analysis used was quantitative analysis, which consisted of path analysis and sign test. The findings of this study indicate that, in sub-structure I, the variable for capital access has a direct positive impact on the business income of household entrepreneurs in Sampe Cita Village. Conversely, in sub-structure II, the technology response variable has an indirect negative effect on their business income, with the inflation variable serving as a mediator.